2022
DOI: 10.1097/md.0000000000029101
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific reference values for the 5th generation cardiac troponin T assay in Chinese children

Abstract: The clinical use of the cardiac troponin T (cTnT) assay was limited to the adult population in the diagnosis and prognosis of myocardial injury. However, emerging studies indicated its significant value in the assessment of pediatric cardiology, and it has been routinely measured in most hospitals. Our study investigated the normative values of cTnT in Chinese children and reported the age-specific 99th percentile cut-off for them.A total of 1280 apparently healthy Chinese children were enrolled in our study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…13 The few research studies that have reported pediatric hs-cTn 99th percentile URLs have suggested important differences from adult URLs but were undertaken in relatively small convenience samples of children and adolescents who were attending clinical care appointments. [14][15][16][17] Therefore, the generalizability of previously reported URLs for hs-cTn assays to healthy children and adolescents in the general US population is unknown.…”
mentioning
confidence: 99%
“…13 The few research studies that have reported pediatric hs-cTn 99th percentile URLs have suggested important differences from adult URLs but were undertaken in relatively small convenience samples of children and adolescents who were attending clinical care appointments. [14][15][16][17] Therefore, the generalizability of previously reported URLs for hs-cTn assays to healthy children and adolescents in the general US population is unknown.…”
mentioning
confidence: 99%